PENGARUH KONSENTRASI DAN CARA APLIKASI IBA (INDOLE BUTIRIC ACID) TERHADAP PERTUMBUHAN BIBIT NANAS (ANANAS COMOSUS [L.] MERR.) ASAL TUNAS MAHKOTA - Rugayah, Rugayah; Anggalia, Itha; Ginting, Yohannes Cahya (JURNAL AGROTROPIKA, 2012)
The research was conducted to determine the effects of IBA concentration on the growth of pineapple seedlings sprout from crown cutting on each applications method. The treatment was arranged in factorial (5x2) in ran-domized block design with three replications. The first factor is the concentration of IBA (0 ppm,100 ppm,200 ppm,400 ppm and 600 ppm). The second factor is the application method of IBA (spraying method and basting method). The results showed that the concentration of 400 ppm IBA effect on leaf width, plant wet weight, and number of primary roots. Treatment of IBA application by basting method of the primary root number more than spraying method. The interaction between concentration and applications method of IBA had no effect on all observed variabels. This study were obtained that the concentration of IBA 400 ppm gives the best growth, Treatment of IBA application by basting method to increase the number of primary roots, but the influence concentration of IBA on the growth of seedlings of pineapple seedling from crown cutting is not determined by applications method of IBA. Key words: Pineapple Seedling, Crown Cutting, IBA